Engineered nasal dry powder for the encapsulation of bioactive compounds. Issue 8 (August 2022) - Baldelli, Alberto; Boraey, Mohammed A.; Oguzlu, Hale; Cidem, Aylin; Rodriguez, Athenea Pascual; Ong, Hui Xin; Jiang, Feng; Bacca, Mattia; Thamboo, Andrew; Traini, Daniela; Pratap-Singh, Anubhav
Highlights: Particle engineering can be used to design stable dry powder to be nasally delivered; Spray and spray freeze drying show the highest control over the properties of dry powders; Highly mucoadhesive polymers are suggested for forming capsules for an enhanced cell uptake; Bulk materials, such as sugars or amino acids, are recommended for a high stability of encapsulated bioactive compounds. Abstract : In this review, we present the potential of nasal dry powders to deliver stable bioactive compounds and their manufacture using spray-drying (SD) techniques to achieve encapsulation. We also review currently approved and experimental excipients used for powder manufacturing for specific target drugs. Polymers, sugars, and amino acids are recommended for specific actions, such as mucoadhesive interactions, to increase residence time on the nasal mucosa; for example, high-molecular weight polymers, such as hydroxypropyl methylcellulose, or mannitol, which protect the bioactive compounds, increase their stability, and enhance drug absorption in the nasal mucosa; and leucine, which promotes particle formation and improves aerosol performance.